High resolution mapping of chromosomal regions controlling resistance to gastrointestinal nematode infections in an advanced intercross line of mice - Behnke, J.M.; Iraqi, F.A.; Mugambi, J.M.M.; Clifford, S.; Nagda, S.M.; Wakelin, D.; Kemp, Stephen J.; Leyden, B.; Gibson, John P. (Springer, 2006)
Fine mapping of quantitative trait loci (QTL) associated with resistance to the gastrointestinal parasite Heligmosomoides polygyrus was achieved on F6/F7 offspring (1076 mice) from resistant (SWR) and susceptible (CBA) mouse strains by selective genotyping (top and bottom 20% selected on total worm count in week 6). Fecal egg counts were recorded at weeks 2, 4, and 6, and the average was also analyzed. Blood packed cell volume in weeks 3 and 6 and five immunological traits (mucosal mast cell protease 1, granuloma score, IgG1 against adult worm, IgG1, and IgE to L4 antigen) were also recorded. On Chromosome 1 single-trait analyses identified a QTL with effects on eight traits located at about 24 cM on the F2 mouse genome database (MGD) linkage map, with a 95% confidence interval (CI) of 20-32 cM established from a multitrait analysis. On Chromosome 17 a QTL with effects on nine traits was located at about 18 cM on the MGD map (CI 17.9-18.4 cM). Strong candidate genes for the QTL position on Chromosome 1 include genes known to be involved in regulating immune responses and on Chromosome 17 genes within the MHC, notably the Class II molecules and tumor necrosis factor.